Testing Bureaucratic Influence on Local School Expenditures by Comparing Survey and Expenditure Data - Wyckoff, Paul Gary (The Review of Economics and Statistics, 1991)
Previous empirical studies of bureaucratic power have employed testing procedures that are sensitive only to complete bureaucratic power in which the bureaucrat is able to force an all or nothing choice on his legislative sponsor. This paper suggests a test for incomplete bureaucratic power in which micro-based, survey estimates of the cost elasticity of demand and marginal propensity to spend out of lump-sum aid are compared with estimates of these same parameters taken from governmental expenditure studies. Empirical tests with 205 non-SMSA school districts in Michigan yield results that are consistent with incomplete bureaucratic power. Copyright 1991 by MIT Press.